The relationship between motivation and learning reading and writing in sixth graders in the Hashemite Kingdom of Jordan - Farid Turki Jeditawi,; Mohd Aderi Che Noh,; Kamarulzaman Abdul Ghani, (Fakulty of Education,UKM, 2011)
This study aims at investigating motivation relationship wirth learning reading and writing in sixth grader in public schools in the Hashemite kingdom of Jordan. This major goal includes the following items: identifying the level of motivation in sixth graders attending public schools in Jordan, identifying their academic achievement in reading and writing, identifyingthe relationship between their level of motivation and their learning and writing,identifying the influence of motivation on their learning reading and writing. The population of the study includes all six-graders in public schools in jordan whereas multi-stages random sampling is used to choose the sample. This sample consists of 852 students,460 males and 392 females. The following tools are used; Herman's achivement motivation questionnaire,achivement test prepared by the researcher. The study has found out that the mean of motivation is above average(3.91), the mean of reading and writing achivement is above average(11.92). The study has also indicated a significant positive correlation between motivation and learning reading and writing (0,268), at (0.01) furthermore,the result have pinpointed the influence of motivation on learning reading and writing, as it explained the figure (7.2%)of the total of explanatory variation for learning reading and writing